2015
DOI: 10.1371/journal.pone.0114495
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Trials for Prevention of Tumor Progression of Hepatocellular Carcinoma by LZ-8 Targeting c-Met Dependent and Independent Pathways

Abstract: Hepatocellular carcinoma (HCC) is among the most lethal cancers. Mounting studies highlighted the essential role of the HGF/c-MET axis in driving HCC tumor progression. Therefore, c-Met is a potential therapeutic target for HCC. However, several concerns remain unresolved in c-Met targeting. First, the status of active c-Met in HCC must be screened to determine patients suitable for therapy. Second, resistance and side effects have been observed frequently when using conventional c-Met inhibitors. Thus, a prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 58 publications
1
22
0
2
Order By: Relevance
“…Here, we showed that the rLZ‐8 induced the Cbl‐mediated clathrin‐dependent degradation of both wt‐ and mut‐EGFR and also exhibited efficacy against lung cancer cells. In contrast, rLZ‐8 did not downregulate other membrane proteins, including transforming growth factor β (TGFβ) receptors, fibroblast growth factor receptor (FGFR) and integrin beta 1, but also induced c‐Met (hepatocyte growth factor receptor) degradation as previous study (data not shown). Moreover, our unpublished data showed that rLZ‐8 also inhibits cell viability and suppresses EGFR expression in various cancer cells, such as breast, head and neck, colon and cervical cancer (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Here, we showed that the rLZ‐8 induced the Cbl‐mediated clathrin‐dependent degradation of both wt‐ and mut‐EGFR and also exhibited efficacy against lung cancer cells. In contrast, rLZ‐8 did not downregulate other membrane proteins, including transforming growth factor β (TGFβ) receptors, fibroblast growth factor receptor (FGFR) and integrin beta 1, but also induced c‐Met (hepatocyte growth factor receptor) degradation as previous study (data not shown). Moreover, our unpublished data showed that rLZ‐8 also inhibits cell viability and suppresses EGFR expression in various cancer cells, such as breast, head and neck, colon and cervical cancer (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Initially, we compared the expression of Hic-5 in several patient-derived HCC cell lines, the phenotypes of which such as cell motility have been characterized [ 20 ]. As shown in Figure 2A , Hic-5 markedly expressed in most of the HCCs such as HCC329, HCC353, HCC365 and HCC372 with average to high motility, slightly expressed in HCC363 with average motility but not in the non-motile HCC340 and HCC374 [ 20 ]. Notably, HCC329, the most motile HCC [ 20 ], expressed the highest Hic-5 among the HCCs examined.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2A , Hic-5 markedly expressed in most of the HCCs such as HCC329, HCC353, HCC365 and HCC372 with average to high motility, slightly expressed in HCC363 with average motility but not in the non-motile HCC340 and HCC374 [ 20 ]. Notably, HCC329, the most motile HCC [ 20 ], expressed the highest Hic-5 among the HCCs examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A protein (Lingzhi-8, LZ-8) from Ganoderma Lucidum was reported that it had anti-tumor activity and could modulate EGFR expression but its binding site on EGFR and mechanism are still unclear [18,19]. Here, we found that recombinant LZ-8 (rLZ-8) could bind to EGFR specifically, induce catastrophic macropinocytosis, enter into HCC cells with EGFR, lead to the blockage of cell membrane recycling and then result in cell death via membrane ruffling, cell membrane over-internalization, cell rounding and bursting.…”
Section: Introductionmentioning
confidence: 99%